TEACHER STRATEGIES USING QUANTUM LEARNING TO IMPROVE SCIENCE LEARNING OUTCOMES IN CLASS IV OF ELEMENTARY SCHOOL OF GMIM 1 KAKASKASEN - Yarona, Sarah Miryam; Rorimpandey, Widdy H. F. (Institut of Shanti Bhuana, 2023)
The research aims to improve science learning outcomes using the Quantum Learning strategy for fourth-grade students at Elementary School GMIM I Kakaskasen. This type of research uses Classroom Action Research (PTK), which consists of 4 stages, namely: 1) Planning, 2) Implementation, 3) observation, and 4) reflection. The subjects of this research were fourth-grade elementary school students. Techniques for collecting data are Observation and tests. These techniques are considered appropriate to the background of the science learning process with material on the structure and function of stems in plants using the Quantum Learning strategy. The research results showed that in the first cycle, the learning outcomes were 73.33% complete, and in the second cycle, it was 92.38%. So, it can be concluded that by implementing the Quantum Learning strategy.